Novel hemotropic mycoplasmas are widespread and genetically diverse in vampire bats - VOLOKHOV, D. V. (Epidemiol Infect, 2017)
Bats (Order: Chiroptera) have been widely studied as reservoir hosts for viruses of concern for human and animal health. However, whether bats are equally competent hosts of non-viral pathogens such as bacteria remains an important open question. Here, we surveyed blood and saliva samples of vampire bats from Peru and Belize for hemotropic Mycoplasma spp. (hemoplasmas), bacteria that can cause inapparent infection or anemia in hosts. 16S rRNA gene amplification of blood showed 67% (150/223) of common vampire bats (Desmodus rotundus) were infected by hemoplasmas. Sequencing of the 16S rRNA gene amplicons revealed three novel genotypes that were phylogenetically related but not identical to hemoplasmas described from other (non-vampire) bat species, rodents, humans, and non-human primates. Hemoplasma prevalence in vampire bats was highest in non-reproductive and young individuals, did not differ by country, and was relatively stable over time (i.e., endemic). Metagenomics from pooled D. rotundus saliva from Peru detected non-hemotropic Mycoplasma species and hemoplasma genotypes phylogenetically similar to those identified in blood, providing indirect evidence for potential direct transmission of hemoplasmas through biting or social contacts. This study demonstrates vampire bats host several novel hemoplasmas and sheds light on risk factors for infection and basic transmission routes. Given the high frequency of direct contacts that arise when vampire bats feed on humans, domestic animals, and wildlife, the potential of these bacteria to be transmitted between species should be investigated in future work.